2020
DOI: 10.15376/biores.15.4.8110-8120
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of methylxanthines based on their properties

Abstract: Wood materials for construction purposes can be attacked by various wood-destroying fungi. An ideal wood-preserving substance is supposed to be environment- and health-friendly. For this reason, the effects of the most relevant and non-toxic methylxanthines, such as caffeine and its metabolites theobromine and theophylline, on fungal growth, together with their degradability related to their properties were analyzed in this study. Agar tests with four wood-destroying fungal species (Serpula lacrymans, Coniopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…and mechanistic insights revealed that it induces membrane damage due to enhanced ionic disturbances and depleted ergosterol levels with a concomitant rise in membrane fluidity due to elevated flippase activity. Regarding the differences in toxicity for fungi among the two methylxanthines, this would result from differences in the dipole moment, lipophilicity, and solubility, as noted by Kobetičová et al [5]. Caffeine is more lipophilic, which correlates with its easier penetration of membranes and possible toxic effects on fungi.…”
Section: On Possible Mechanisms Of Actionmentioning
confidence: 96%
See 2 more Smart Citations
“…and mechanistic insights revealed that it induces membrane damage due to enhanced ionic disturbances and depleted ergosterol levels with a concomitant rise in membrane fluidity due to elevated flippase activity. Regarding the differences in toxicity for fungi among the two methylxanthines, this would result from differences in the dipole moment, lipophilicity, and solubility, as noted by Kobetičová et al [5]. Caffeine is more lipophilic, which correlates with its easier penetration of membranes and possible toxic effects on fungi.…”
Section: On Possible Mechanisms Of Actionmentioning
confidence: 96%
“…and Phoma violacea (Bertel) Eveleigh. Kobetičová et al [5] tested the activity of both caffeine and theophylline at a concentration of 2000 µg mL −1 against Coniophora puteana (Schumach.) P.…”
Section: Comparison With Reported Antifungal Activities Of Methylxant...mentioning
confidence: 99%
See 1 more Smart Citation
“…globosum ), wood-staining fungi ( A. pullulans and S. pythiophila ), and molds ( A. niger , A. terreus , C. herbarum , P. variotii , P. cyclopium , P. funiculosum , P. brevicompactum , P. violacea , and T. viride ) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Kobetičová et al [ 46 ] assessed the effect of non-toxic methylxanthines including caffeine and its metabolites—theobromine and theophylline on the growth of four wood-destroying fungal species ( S. lacrymans , C. puteana , G. sepiarium , and T. versicolor ) in the agar test. The results indicated that caffeine exhibited a 100% inhibitory effect on all fungal strains, in contrast to theobromine, which was not effective in this regard.…”
Section: Plant-derived Antifungal Agentsmentioning
confidence: 99%
“…Lightly permeable types of pine and beech wood and the method of vacuum impregnation [7,11,12] were used in most cases, but efficiency on hard-to-permeate spruce wood was also verified using long-term dipping technology [13]. Caffeine was effective against the growth of wood-destroying white and brown rot fungi [6][7][8]10,12,14] and was also tested on wooden specimens for mould growth [15]. So far, a 2% caffeine solution was tested as an effective concentration, whereas tests using lower concentrations that would reduce the cost of the used protection [1,16] are lacking.…”
Section: Introductionmentioning
confidence: 99%